When financial performance of Islamic banks matters: The moderating effect of islamic social reporting - Putri, Alisa; Setiyowati, Supami; Tyasari, Irma (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2023)
The purpose of this study is to adjust how the moderation of Islamic social reports impacts liquidity, leverage, business size, and asset turnover on financial performance. The purposive sampling method was used to collect fifty samples from Islamic commercial banks registered with the Financial Services Authority from 2013 to 2022. Data analysis was performed with the Statistics Program for Social Sciences, also known as SPSS. The results of the study show that liquidity and leverage do not affect financial performance; conversely, firm size and activity ratio affect financial performance. However, Islamic social reports can control liquidity, business size, and asset turnover on financial performance. Tujuan dari pengkajian ini adalah untuk mengetahui efek moderasi laporan sosial Islam berdampak pada likuiditas, leverage, ukuran bisnis, dan perputaran aset terhadap kinerja keuangan. Metode purposive sampling digunakan untuk mengumpulkan lima puluh sampel dari bank umum syariah yang terdaftar di Otoritas Jasa Keuangan sejak 2013 hingga 2022. Analisis data menggunakan teknik analisis statistik deskriptif, uji asumsi klasik, uji regresi dan uji hipotesis berganda dengan bantuan SPSS. Hasil pengkajian menunjukkan bahwa likuiditas dan leverage tidak mempengaruhi kinerja keuangan; sebaliknya, ukuran perusahaan dan rasio aktivitas mempengaruhi kinerja keuangan. Namun, laporan sosial Islam dapat memoderasi likuiditas, ukuran bisnis, dan perputaran aset terhadap kinerja keuangan.